MANAGING CULTURAL HERITAGE WITH AI: THE CASE OF FELT ART - Kairanbay T. Z.; Zholdubaeva A.K. (Interdisciplinary Science Studies, 2025)
This study explores the intersection of artificial intelligence, intangible cultural heritage, and traditional felt craft, explicitly focusing on Kazakh felt art as a living expression of nomadic identity. Using a bibliographic analysis of peer-reviewed literature indexed in Scopus (2005–2025), the research identifies key thematic trends, methodological approaches, and regional patterns in applying AI to heritage contexts. The findings reveal a significant growth in scholarly interest, particularly in recent years, and highlight Central Asia, especially Kazakhstan and Kyrgyzstan, as an emerging contributor to the global digital heritage and craft preservation discourse. Through semantic mapping and thematic clustering, the study demonstrates how felt art serves as a cultural practice and a conceptual bridge linking technological innovation with indigenous knowledge systems. While AI presents promising tools for preserving and promoting endangered crafts, the study also identifies critical gaps, especially in locally grounded, ethically informed applications. This research contributes to rethinking the role of AI in cultural heritage management, calling for more context-sensitive, community-based, and culturally literate approaches to technological integration